2007
DOI: 10.1093/aje/kwm300
|View full text |Cite
|
Sign up to set email alerts
|

Problems with Condom Use among Patients Attending Sexually Transmitted Disease Clinics: Prevalence, Predictors, and Relation to Incident Gonorrhea and Chlamydia

Abstract: Condom use remains important for sexually transmitted disease (STD) prevention. This analysis examined the prevalence of problems with condoms among 1,152 participants who completed a supplemental questionnaire as part of Project RESPECT, a counseling intervention trial conducted at five publicly funded STD clinics between 1993 and 1997. Altogether, 336 participants (41%, 95% confidence interval: 38, 45) reporting condom use indicated that condoms broke, slipped off, leaked, or were not used throughout interco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 56 publications
3
37
1
Order By: Relevance
“…These problems range from those that could directly compromise effectiveness within a particular act of intercourse (e.g. breakage, slippage and failure to use condoms throughout intercourse) 18,20,24,55 to those that can directly impact the likelihood of condom use during future acts of intercourse (e.g. loss of erection, loss of sensation or inability to ejaculate).…”
Section: Correct Usementioning
confidence: 99%
See 2 more Smart Citations
“…These problems range from those that could directly compromise effectiveness within a particular act of intercourse (e.g. breakage, slippage and failure to use condoms throughout intercourse) 18,20,24,55 to those that can directly impact the likelihood of condom use during future acts of intercourse (e.g. loss of erection, loss of sensation or inability to ejaculate).…”
Section: Correct Usementioning
confidence: 99%
“…[55][56][57][58] Two intentional user practices that have received increased attention of late -putting condoms on after starting intercourse or removing condoms before ejaculation 20,55,[59][60][61][62][63] -illustrate well the challenges of achieving effective use. And although the rate of any of single condom problem generally is low (less than 5-10% of coital acts), 55,59 the fraction of users reporting one or more problems often exceeds 40-50% even over brief periods of time. 55,62 These examples underscore the reality that condom use, despite features that give an appearance of simplicity (e.g.…”
Section: Correct Usementioning
confidence: 99%
See 1 more Smart Citation
“…This second point is better illustrated by a prospective study of 132 clinic attendees tested for chlamydia and gonorrhoea at the beginning and end of a 3-month interval. 43 Although the small sample size precludes meaningful CI, the descriptive information from this study was intriguing. Among 18 people reporting consistent use of condoms in the recall period and a lack of problems (slippage, breakage, leaking, early removal, late application), none acquired either chlamydia or gonorrhoea.…”
Section: Chlamydia and Gonorrhoeamentioning
confidence: 88%
“…Several prospective studies of condom effectiveness against gonorrhoea have been published; 20,36,[43][44][45][46] however, most of these are substantially underpowered, making the standard use of 95% CI a severe handicap to testing the null hypothesis fairly. Nonetheless, two of these six studies observed a significant protective effect.…”
Section: Gonorrhoeamentioning
confidence: 99%